The Development of Empathic Concern in Siblings: A Reciprocal Influence Model. Issue 5 (20th February 2018) - Jambon, Marc; Madigan, Sheri; Plamondon, André; Daniel, Ella; Jenkins, Jennifer M.
Abstract : This study utilized actor–partner interdependence modeling to examine the bidirectional effects of younger ( M age  = 18 months) and older siblings ( M age  = 48 months) on later empathy development in a large ( n  = 452 families), diverse (42% immigrant) Canadian sample. Controlling for parenting, demographic characteristics, sibling relationship quality, and within‐child stability in empathic concern, both younger and older siblings' observed empathic concern uniquely predicted relative increases in the other's empathy over a period of 18 months. The strength of the partner effects did not differ by birth order. Sex composition moderated the younger sibling partner effect, whereas age gap moderated the older sibling partner effect. This study highlights the important role that siblings play in enhancing the development of care and concern for others.